Social network factors as correlates and predictors of high depressive symptoms among Black men who have sex with men in HPTN 061 - Latkin, Carl (AIDS Behav, 2017)
Depression is linked to a range of poor HIV-related health outcomes. Minorities and men who have sex with men (MSM), suffer from high rates of depression. The current study examined the relationship between depressive symptoms and social network characteristics among community-recruited Black MSM in HPTN 061 from 6 US cities. A social network inventory was administer at baseline and depression was assessed with the CES-D at baseline, 6, and 12-months. At baseline, which included 1167 HIV negative and 348 HIV positive participants, size of emotional, financial, and medical support networks were significantly associated with fewer depressive symptoms. In longitudinal mixed models, size of emotional, financial, and medical support networks were significantly associated with fewer depressive symptoms as was the number of network members seen weekly. In the multivariate analyses, size of medical appointment network remained statistically significant (aOR= 0.89, CI=0.81-0.98). These findings highlight the importance of network support of medical care on depression and suggest the value of support mobilization.